PERBANDINGAN HUKUM PERLINDUNGAN DATA PRIBADI DI INDONESIA - MALAYSIA - Saudatina Sekar Arum; Aminullah (As-Sulthan Journal of Education, 2026)
The development of information technology has driven the increasing need for personal data protection as part of human rights and legal certainty. Indonesia and Malaysia, as developing countries in Southeast Asia, have established personal data protection regulations, but with different legal system characteristics and policy approaches. This article aims to analyze the comparative nature of personal data protection laws in Indonesia and Malaysia, focusing on regulatory aspects, oversight institutions, and law enforcement mechanisms. This article uses a normative legal research method with comparative law. The analysis shows that Malaysia has a more mature personal data protection system in terms of institutions and law enforcement, while Indonesia is still in the stage of strengthening regulatory implementation. This article is expected to serve as an academic and practical reference in the development of personal data protection laws in Indonesia.